2015
DOI: 10.1073/pnas.1519159112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of transcriptome diversity in Drosophila melanogaster

Abstract: Understanding how DNA sequence variation is translated into variation for complex phenotypes has remained elusive but is essential for predicting adaptive evolution, for selecting agriculturally important animals and crops, and for personalized medicine. Gene expression may provide a link between variation in DNA sequence and organismal phenotypes, and its abundance can be measured efficiently and accurately. Here we quantified genome-wide variation in gene expression in the sequenced inbred lines of the Droso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
133
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(151 citation statements)
references
References 57 publications
16
133
2
Order By: Relevance
“…As expected from previous studies of gene expression using pools of individuals, we observed massive differences in gene expression due to sex (Table 1 and Table S1) (Jin et al 2001; Arbeitman et al 2002; Parisi et al 2003; Ranz et al 2003; Harbison et al 2005; Wayne et al 2007; Zhang et al 2007; Ayroles et al 2009; Huylmans and Parsch 2014; Huang et al 2015). Of the 15,674 genes detected in the experiment, 14,883, or 95%, were differentially expressed between males and females (FDR < 0.05).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As expected from previous studies of gene expression using pools of individuals, we observed massive differences in gene expression due to sex (Table 1 and Table S1) (Jin et al 2001; Arbeitman et al 2002; Parisi et al 2003; Ranz et al 2003; Harbison et al 2005; Wayne et al 2007; Zhang et al 2007; Ayroles et al 2009; Huylmans and Parsch 2014; Huang et al 2015). Of the 15,674 genes detected in the experiment, 14,883, or 95%, were differentially expressed between males and females (FDR < 0.05).…”
Section: Resultssupporting
confidence: 87%
“…Duplicate libraries prepared for 118 flies indicated that the technical effects were very small relative to the biological effects (Lin et al 2016). In addition, residual heterozygosity in chromosomal inversions does not appear to be a factor, in agreement with a recent assessment of gene expression in pooled flies of the DGRP (Huang et al 2015). Thus, the biological sources of gene expression differences among individuals are much greater than these potential technical sources.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although high, this amount of variation in Z. tritici remains comparable to former results coming from many other studies highlighting the natural variation of transcription within species, mostly using eQTL mapping ( e.g. Brem, 2002; Schadt et al, 2003; Huang et al, 2015; Zan et al, 2016; Osada et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…GSE67505). The expression data 492 was obtained from pooled RNA-Seq data for the DGRP2 lines, as described in the original 493 study [43]. The published expression tables are given separately for male and females in FPKM 494…”
Section: Gene Expression and Codon Usage Data 491mentioning
confidence: 99%